Penguatan Lembaga Adat Tuha Peut dalam Penyelesaian Perselisihan Masyarakat Aceh - Rahmito Azhari; Wahyu Ramadhani; Fahrul Reza (Universitas Muhammadiyah Yogyakarta, 2023)
The life of customs and customary law in Acehnese society is emphasized in Law Number 11 of 2006 concerning the Government of Aceh (UUPA), namely in Article 98 of the LoGA which regulates the duties, authorities, rights and obligations in carrying out the development of traditional life and customs by establishing a Aceh Qanun. Tuha Peut Gampong has not played a good role in resolving community disputes. ). The tuha peut institution consists of four elements, namely elements of ulama, adat, clever people, and community leaders. The authorities of tuha peut include appointing and dismissing geuchik, compiling reusam gampongs, supervising and resolving disputes that occur in the community. In Aceh, there are still many customary disputes that have not been resolved in the customary settlements in the gampong and many have been reported by the community to the police. This is also due to the lack of knowledge of the Tuha Peut Customary Institution in resolving disputes at the gampong level. This study aims to identify the role of Tuha Peut Gampong as a gampong consultative body in the process of resolving community disputes, to find out the obstacles that cause Tuha Peut Gampong to have not played a good role in resolving disputes that occur in the community, and to find out the efforts made to strengthen the role of Tuha Peut Gampong. Gampong in the settlement of community disputes. The data in this study were obtained from literature review and field research. A literature review was conducted to obtain secondary data by studying the literature and applicable laws and regulations.